2021
DOI: 10.1002/jbm4.10557
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole‐Associated Periostitis: New Insights into Pathophysiology and Management

Abstract: Voriconazole‐associated periostitis (VAP) is an underrecognized and unpredictable side effect of long‐term voriconazole therapy. We report two cases of VAP occurring in the post‐transplant setting: a 68‐year‐old lung transplant recipient who required ongoing voriconazole therapy, in whom urinary alkalinization was used to promote fluoride excretion and minimize voriconazole‐related skeletal toxicity, and a 68‐year‐old stem‐cell transplant recipient with a high voriconazole dose requirement, identified on pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…When voriconazole is the agent of choice, these individuals can be exposed to higher cumulative doses of the drug and are at higher risk of developing periostitis. Interestingly, periostitis has only been observed with voriconazole, which has three fluoride ions compared with the difluorinated azoles, fluconazole and posaconazole 1 13. The additional fluoride ion is proposed to cause hyperfluorosis, with excess fluoride taken up by calcified tissues; this drives new periosteal bone formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When voriconazole is the agent of choice, these individuals can be exposed to higher cumulative doses of the drug and are at higher risk of developing periostitis. Interestingly, periostitis has only been observed with voriconazole, which has three fluoride ions compared with the difluorinated azoles, fluconazole and posaconazole 1 13. The additional fluoride ion is proposed to cause hyperfluorosis, with excess fluoride taken up by calcified tissues; this drives new periosteal bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased fluoride has also been shown to decrease the resorption activity of newly formed osteoclasts, causing an imbalance in bone remodelling 14 15. A study comparing fluoride levels in patients treated with different triazoles showed that mean serum fluoride levels in the voriconazole group were significantly higher than those treated with itraconazole or fluconazole but not posaconazole 13…”
Section: Discussionmentioning
confidence: 99%